Uncovering the chain of corruption: A Case Study in Bangladesh - Hossan, Md. Alomgir; Abdur Rohim Sourav; Jakirul Islam (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
Government officials are responsible to the people because they are paid for their services by the fund of the country which is collected from people. They got extra facilities as the government officials but people see them as the oppressors while taking public services. Their offensive behavior hurts the common people who do not have extra money paid for services. This study attempts to make the people aware, conscious, responsible, accountable, and transparent to government officials. The study titled